2001
DOI: 10.1016/s0168-0102(01)00225-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-images in the video monitor coded by monkey intraparietal neurons

Abstract: When playing a video game, or using a teleoperator system, we feel our self-image projected into the video monitor as a part of or an extension of ourselves. Here we show that such a self image is coded by bimodal (somatosensory and visual) neurons in the monkey intraparietal cortex, which have visual receptive fields (RFs) encompassing their somatosensory RFs. We earlier showed these neurons to code the schema of the hand which can be altered in accordance with psychological modification of the body image; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
107
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 207 publications
(117 citation statements)
references
References 37 publications
10
107
0
Order By: Relevance
“…For example, previous neurophysiological studies on monkeys proposed that the intraparietal cortex was a neural substrate in which the representation of the body schema is extended by tool handling (Iriki et al, 1996(Iriki et al, , 2001. In fMRI studies on humans, the neural correlates for the perception of body-object interactions were observed in the posterior parietal regions (Naito and Ehrsson, 2006;Naito et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous neurophysiological studies on monkeys proposed that the intraparietal cortex was a neural substrate in which the representation of the body schema is extended by tool handling (Iriki et al, 1996(Iriki et al, , 2001. In fMRI studies on humans, the neural correlates for the perception of body-object interactions were observed in the posterior parietal regions (Naito and Ehrsson, 2006;Naito et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…One could argue that manipulation of the camera rake could be achieved simply by remapping sensorimotor coordination-much as one adjusts to wearing deviating prism glasses and quickly resumes using correct reaching angles, as the monkeys were already probed to be capable of remapping their body parts (hand) and the target object (food) on the artiWcial device (monitor) (Iriki et al 2001). In fact, the time courses of the number of pulling-back the camera rake (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic recordings of single neuron activities were made from the hand-arm region of the anterior bank of the intraparietal sulcus (a posterior extension of the first somatosensory cortex, SI) in twelve hemispheres, using a microelectrode technique described previously (Iwamura et al, 1993). These monkeys were the same animals we had used for our previous reports (Iriki et al, 1996b;Iriki et al, 2001;Obayashi et al, 2000). Thus they were trained to use rake-shaped tools (n=8) and also a video monitor (n=5) to retrieve food.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, in human patients, lesions in this brain area are known to cause impairment of the body schema (Head & Holmes, 1911), which makes it difficult for the patient to achieve purposeful hand movements in the dark or without seeing, i.e., without visual guidance. A growing number of monkey experiments have reported the existence of "bimodal neurons" that respond to both somatosensory and visual stimuli in the peri-intraparietal cortices including the ventral intraparietal (VIP) area Colby, Duhamel, & Goldberg, 1993;Duhamel, Colby, & Goldberg, 1991, 1998, the medial intraparietal (MIP) area Graziano & Gross, 1998;Rizzolatti, Fogassi, & Gallese, 1997), and the anterior bank of the lateral intraparietal sulcus (Iriki, Tanaka, & Iwamura, 1996b;Iriki, Tanaka, Obayashi, & Iwamura, 2001;Obayashi, Tanaka, & Iriki, 2000). These studies have indicated that the intraparietal areas are the sites of visuosomatosensory integration.…”
Section: Yoshiaki Iwamuramentioning
confidence: 99%
See 1 more Smart Citation